The disposition of oral and intramuscular pyrimethamine/sulphadoxine in Kenyan children with high parasitaemia but clinically non-severe falciparum malaria. - Winstanley, P; Watkins, WM; Newton, C; Nevill, C; Mberu, E; Warn, P; Waruiru, C; Mwangi, I; Warrell, D; Marsh, K (1992)
1. H.p.l.c. methods are described for the measurement of pyrimethamine and sulphadoxine in small volumes of plasma dried on filter paper strips. 2. Pyrimethamine/sulphadoxine (Fansidar, Hoffman LaRoche) was given by mouth and by intramuscular injection to children with uncomplicated falciparum malaria but with high parasitaemia (n = 8 for both routes; pyrimethamine 1.25 mg kg-1, sulphadoxine 25 mg kg-1). 3. Plasma concentrations of pyrimethamine and sulphadoxine associated with synergistic effects against pyrimethamine-resistant strains of Plasmodium falciparum in vitro were achieved within 1 h of administration and were maintained beyond the end of sampling. 4. After both oral and parenteral administration the plasma concentrations of both compounds were lower than those predicted by data from healthy subjects. 5. Areas under the plasma concentration-time curves of sulphadoxine after oral and i.m. administration did not differ significantly, although maximum plasma drug concentrations were higher after the i.m. route (P = 0.03). 6. The AUC values of pyrimethamine did not differ significantly between the two routes of administration. However, after i.m. administration AUC(0,24 h) values were smaller (P = 0.03), and the time to maximum plasma drug concentration (tmax) was longer (P = 0.004) than when the drug was given orally.